AN EXPLANATORY PROCESS OF DESIGNING AN EFFECTIVE SYLLABUS FOR AMBULANCE PRACTITIONERS - Uralova, Nozima (Журнал иностранных языков и лингвистики, 2021)
This work describes the importance and the steps of the research conducted in teaching English to Ambulance Service workers. The research aimed to identify the needs of medical practitioners and design a syllabus that could help them to improve their language skills for specific purposes. Triangulated needs analysis revealed the needs, demands, and aims of the target population. Based on the findings of the research, an ESP course and syllabus were designed.